2014
DOI: 10.1128/aem.00793-14
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry and Real-Time Quantitative PCR as Tools for Assessing Plasmid Persistence

Abstract: The maintenance of a plasmid in the absence of selection for plasmid-borne genes is not guaranteed. However, plasmid persistence can evolve under selective conditions. Studying the molecular mechanisms behind the evolution of plasmid persistence is key to understanding how plasmids are maintained under nonselective conditions. Given the current crisis of rapid antibiotic resistance spread by multidrug resistance plasmids, this insight is of high medical relevance. The conventional method for monitoring plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Since only cells will be stained and not small particles this allows correct quantification of GFP ‐ cells. The second challenge described in the published study is the overestimation of replicon stability caused by continued fluorescence of the stable GFP after replicon loss [65]. The obvious solution to this problem we present here is the use of unstable GFP variants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since only cells will be stained and not small particles this allows correct quantification of GFP ‐ cells. The second challenge described in the published study is the overestimation of replicon stability caused by continued fluorescence of the stable GFP after replicon loss [65]. The obvious solution to this problem we present here is the use of unstable GFP variants.…”
Section: Discussionmentioning
confidence: 97%
“…While GFP encoded on secondary replicons was used before to detect respective copy numbers we use it here to measure replicon stability [36]. A very recent study describes a similar approach [65]. One challenge they experienced is the separation of GFP ‐ cells from background caused by small particles in the used buffer.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the stability data for 6475-CBRluc-mCherry generated by both FCM and PC were similar and indicated 100% plasmid loss at day 4 ( Fig 3A ). Loftie-Eaton et al have also found that the plasmid persistence profiles generated by these techniques are similar [ 34 ]. However, the plasmid loss rate of 6475- mCherry detected by PC was clearly higher than the rate shown by FCM.…”
Section: Discussionmentioning
confidence: 99%
“…The fraction of plasmid‐bearing cells in each culture was estimated via quantitative PCR (qPCR; Loftie‐Eaton, Tucker, Norton, & Top, ) of the plasmid‐encoded trfA gene (encoding the replication initiation protein) and the chromosomally encoded 16S rRNA genes. Plasmid pB10 has a low copy number (~2 per cell, data not shown), and the number of 16S rRNA gene copies in Acinetobacter baumannii is five (Maslunka, Carr, Gürtler, Kämpfer, & Seviour, ; Stoddard, Smith, Hein, Roller, & Schmidt, ).…”
Section: Methodsmentioning
confidence: 99%